Tanggung Jawab Notaris yang Aktanya Dibatalkan karena Cacat Yuridis (Studi Kasus Putusan Kasasi MA No. 320 K/PDT/2013) - Rhyzky Dewan Hutomo (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2018)
Notary Profession, as law enforcement, requires a responsibility, either individually or socially. Because of its very fundamental position, in performing its duty to make an authentic deed, a notary must perform the provisions contained in the Law of Notary, in addition to being honest, thorough, independent, impartial and guarding the interests of the parties concerned in legal action, so it must act carefully, meticulously, and thoroughly in carrying out procedures in making an authentic deed. Otherwise, it will result in an authentic deed not having a perfect verifying force value (volledig) and binding (bindende), or the degradation of its evidentiary power or it may be void, commonly called an authentic deed with a juridical defect. As a public official, a Notary is authorized to create an authentic deed, which can be held responsible for his conduct. The responsibility of a Notary as a Public Official includes the responsibility of the Notary profession itself relating to the deed. In relation to its authority the Notary may be held responsible for his deeds in making authentic deeds. The forms of responsibility of a notary are: (1) the responsibility of a notary publicly, (2) a criminal notary's responsibility, (3) a notarial responsibility based on a notary regulation, and (4) a notarial responsibility under the Notary Code of Ethics